2018
DOI: 10.1016/j.jvs.2017.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and management costs of peripheral arterial disease in France

Abstract: Mortality is elevated and cardiovascular events are frequent among French PAD patients. PAD drug treatment guidelines are not fully implemented in France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is also interesting to note that the percentage of revascularization is particularly high (68%). This is not surprising given the rates of endovascular and surgical revascularization of patients with PAD, which exceed 10% per year in France [16], whereas the data presented here concerns the history of revascularization without time limit.…”
Section: Discussionmentioning
confidence: 69%
“…It is also interesting to note that the percentage of revascularization is particularly high (68%). This is not surprising given the rates of endovascular and surgical revascularization of patients with PAD, which exceed 10% per year in France [16], whereas the data presented here concerns the history of revascularization without time limit.…”
Section: Discussionmentioning
confidence: 69%
“…Comparable results were found recently by others. 17,18,20 Moreover, the severe risk profile of CLI patients due to comorbidities such as chronic kidney disease and the lack of specific guidelines could have decreased the initiation of therapies by physicians in primary care before hospitalization. 21 Recently, a Swedish study showed that patients with PAD are less intensively treated than those with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PAD prevalence is very likely underestimated as studies suggest that up to half of the patients suffering from PAD are asymptomatic [2][3][4]. With an aging population, PAD is a significant public health issue and a financial burden on the wider society [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%